Denitrification of Activated Sludge in The Presence of Different Organic Substrates - Agustiyani, Dwi; Yamagishi, Takao (BRIN, 2004)
The effect of organic carbon denitrifying activity was studied in batch reactor. Fom reactors were operated in parallel under anoxic condition in four different donor electrons. which were acetic acid (Reactor A), methanol (Reactor M), phenol (Reactor P), and glucose (Reactor G). The reactors were fed with the artificial waste, which contain 721.8 mg/l NaNO3. The concentration organic carbon added to the reactors were varied from TOD:N ratio of 0.5:1; 1: 1, 1.5:1, to 2:1. The denitrification activity was estimated by measuring the reduction rate of nitrogenous oxide and N2O gas production. The denitrification capacity of adapted-sludge was also investigated, and the rates were estimated from the cumulative N2O (without acetylene inhibition) and N2 gas production. Reduction rate of nitrogenous oxide in all reactors increased during the investigation; lhe increase reduction rate were correlated to the increase of organic carbon concentration. The maximum reduction rate of nitrogenous oxide in Reactor A was higher than those of the others. However, reduction rate in Reactor M was more constant, so that nitrogenous oxides existed in this reactor was removed faster. The highest potential denitrification rate (N20 production) was observed in sludge of Reactor A. However, N2 gas recovery trom nitrate and nitrite transformed by sludge of Reactor M was the highest. Linear correlation between nitrogenous oxide reduction with gas production was observed in Reactor A, M and P, but not in Reactor G.